Hacia una didáctica de la lengua minorizada en contextos de asimilación lingüística. Algunas aportaciones desde la teoría - Campos, I.O. (2018)
Nowadays, in the European territories, about 120 langauges have the status of regional or minority languages and only 10% of world’s languages are out of danger of disappearing. One of the main areas to protect minority languages is the educational one. Nevertheless, there are still some plurilingual states and/or territories that have not given to their regional languages the status they need in order not to disappear in the future. In the schools of these territories, where multilingual education is not developed and the language is taught as a subject, it is important to consider some didactical characteristics that can improve the situation of that regional and minoritized languages. In order to uderline these keys we have reviewed the works of Arnau (2005) and Mendoza (2005) and also the principles of the Sociodidactics of Languages.